Hypophosphatemia Associated with Intravenous Iron Therapies for Iron Deficiency Anemia: A Systematic Literature Review - Glaspy JA; Lim-Watson MZ; Libre MA; Karkare SS; Hadker N; Bajic-Lucas A; Strauss WE; Dahl NV (Dove Medical Press, 2020)
John A Glaspy,1 Michelle Z Lim-Watson,2 Michael A Libre,3 Swagata S Karkare,3 Nandini Hadker,3 Aleksandra Bajic-Lucas,2 William E Strauss,2 Naomi V Dahl2 1UCLA School of Medicine, Los Angeles, CA, USA; 2AMAG Pharmaceuticals, Inc., Waltham, MA, USA; 3Trinity LifeSciences, Waltham, MA, USACorrespondence: Naomi V DahlAMAG Pharmaceuticals, Inc., 1100 Winter Street, Waltham, MA 02451, USATel +1 617-498-7650Email ndahl@amagpharma.comBackground: Iron deficiency anemia (IDA) is a prevalent yet underdiagnosed condition with a significant impact on quality of life. Oral iron supplementation is often poorly tolerated or yields inadequate response, requiring the use of intravenous iron (IVI) in some patients. Administration of certain IVI preparations has been associated with decreases in serum phosphate levels and clinically significant hypophosphatemia, which has been reported to lead to adverse events including serious fatigue and osteomalacia.Objective: The purpose of this study was to systematically assess the prevalence, clinical consequences, and reporting of treatment-emergent hypophosphatemia within literature investigating IVI therapies marketed in the United States (US).Methods: A systematic literature review (SLR) was conducted using the PubMed database to identify publications reporting serum phosphate levels or rates of hypophosphatemia within adult IDA patient populations receiving current US-marketed IVIs.Results: The SLR yielded 511 unique publications, with 40 records meeting the final inclusion criteria. Most studies did not report phosphate monitoring methodology or an explicit definition of hypophosphatemia. Hypophosphatemia rates ranged from 0.0% to  92.1% for ferric carboxymaltose (FCM), 0.0% to  40.0% for iron sucrose, 0.4% for ferumoxytol, and 0.0% for low-molecular-weight (LMW) iron dextran. Randomized controlled studies described hypophosphatemia as “asymptomatic” or did not report on other associated sequelae. Eleven case reports detailed treatment-emergent hypophosphatemia in patients treated with FCM. Patients with acute hypophosphatemia primarily developed severe fatigue; those with repeated FCM dosing developed chronic hypophosphatemia associated with osteomalacia and bone deformities.Conclusion: Studies analyzed in this SLR reported a range of hypophosphatemia rates, with the highest consistently seen in patients treated with FCM. Across the clinical literature, there appeared to be minimal standardization of phosphate monitoring and definitions of hypophosphatemia. Although multiple cases have documented serious clinical consequences of hypophosphatemia associated with certain IVIs, current trials neither consistently nor adequately assess the frequency and severity of treatment-emergent hypophosphatemia and may underestimate its prevalence.Keywords: IDA, phosphate, hypophosphatemia, iron supplementation